Metsulfuron-methyl Herbicide on Dehydrogenase and Acid Phosphatase Enzyme Activity on Three Different Soils - Das, Shaon Kumar; Mukherjee, Irani; Das, Suvo Kumar (International Journal of Bio-resource and Stress Management, 2017)
An experiment was conducted during the year 2012−13 to investigate the effects of metsulfuron-methyl herbicide on dehydrogenase and acid phosphatase activity on three diverse soils at two doses (4 and 6 g a.i. ha-1). Different soils exhibited different rates of recovery of soil dehydrogenase and acid phosphatase activity in a period of 15 days after application. Initial dehydrogenase value 1.26, 1.17 and 1.11 reached to final 1.28, 1.14 and 1.03 at lower dose; initial dehydrogenase value 1.26, 1.17 and 1.11 reached to final 1.24, 1.09 and 0.97 at higher, respectively for entisol, mollisol and inceptisol. Similarly, Initial acid phosphate value 1.30, 1.28 and 1.31 reached to final 1.26, 1.28 and 1.26 at lower dose; initial acid phosphate value 1.30, 1.28 and 1.31 reached to final 1.26, 1.22 and 1.25 at higher, respectively for entisol, mollisol and inceptisol. In this study metsulfuron-methyl exerted an initial adverse effect on both enzyme activity but dehydrogenase activity restored in due course of time in each soil. To prevent adverse effects especially in Inceptisol a higher recommended dose of 6 g a.i. ha-1 should be avoided. Recovery was faster in all the three types of soil at the lower dose. Lower recommended dose of 4 g a.i. ha-1 of metsulfuron-methyl would not significantly affect Entisol and Mollisol while in Inceptisol the recovery process was slower and can be accelerated by the addition of organic matter to the soil. At a higher dose of 6 g a.i. ha-1, the dehydrogenase activity recovery rate in all the soils types was slow.